BENTUK SAJIAN TARI BEDHAYA GEHING KARYA THERESIA SRI KURNIATI - Sonia Pangesti Lambangsari; Sri Rochana Widyastutieningrum (Institut Seni Indonesia Surakarta, 2021)
This article discusses the Bedhaya Ge-Hing dance by Theresia Sri Kurniati .Its main focus is on the aspects of process and form. Using the theory of process by Wallas in Utami Munandar book and theory of form by Y. Sumandiyo Hadi. Writing this thesis using qualitative research methods. Data collection techniques used were observation, interview, and literature study. The results showed that the Bedhaya Ge-Hing dance has the characteristics of process and form in accordance with the ideas of choreographer.